High hamstring tendinopathy in runners: Meeting the Challenges of Diagnosis, Treatment, and Rehabilitation - Fredericson, M.; Moore, W.; Guillet, M.; Beaulieu, C. (The Physician and Sportsmedicine, 2005)
High hamstring tendinopathy is an uncommon overuse injury seen in running athletes. Patients typically report deep buttock or thigh pain. A detailed physical examination and, occasionally, imaging studies are necessary to confirm the diagnosis. Rehabilitation involves soft-tissue mobilization, frequent stretching, and progressive eccentric hamstring strengthening and core stabilization exercises. In recalcitrant cases, an ultrasound-guided corticosteroid injection into the tendon sheath can be helpful, and, occasionally, surgery may be necessary to release the scar tissue around the proximal hamstring muscles and the sciatic nerve.